PENGARUH ICE BREAKING TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 112 PARBANGUNAN - Selly Syah Lestari; Parulian Siregar; Junita Irawati (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This research aims to determine the effect of ice breaking on the learning motivation of fourth grade students at SD Negeri 112 Parbangunan. This research was conducted at SD Negeri 112 Parbangunan. The research method used was an experiment with a nonequivalent kontrol group design. Sample collection was carried out using total sampling. The sample for this research consisted of 28 students, for the experimental class, 16 students who were given treatment, namely by applying ice breaking, and for the control class, 12 students who used conventional learning. Analysis of the process data for both groups using the t-test obtained a t-count result of 3.611 and t-table with 5% significance level is 2.05 then t-count>t-table. This shows that there is an influence of ice breaking on the learning motivation of class IV students at SD Negeri 112 Parbangunan.